Waste management and recycling in the former Soviet Union the City of Bishkek, Kyrgyz Republic (Kyrgyzstan) - Sim, Natasha M (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2013)
The UN-Habitat Integrated Sustainable Waste Management (ISWM) benchmarking methodology was applied to profile the physical and governance features of municipal solid waste (MSW) management in the former Soviet Union city of Bishkek, capital of the Kyrgyz Republic. Most of the ISWM indicators were in the expected range for a low-income city when compared with 20 reference cities. Approximately 240,000 t yr(-1) of MSW is generated in Bishkek (equivalent to 200 kg capita(-1) yr(-1)); collection coverage is over 80% and 90% of waste disposed goes to semi-controlled sites operating with minimal environmental standards. The waste composition was a distinctive feature, with relatively high paper content (20-27% wt.) and intermediate organic content (30-40% wt.). The study provides the first quantitative estimates of informal sector recycling, which is currently unrecognised by the city authorities. Approximately 18% wt. of generated MSW is recycled, representing an estimated annual saving to the city authorities of US$0.7-1.1 million in avoided collection/disposal costs. The waste management system is controlled by a centralised municipal waste enterprise (Tazalyk); therefore, institutional coherence is high relative to lower-middle and low-income cities. However, performance on other governance factors, such as inclusivity and financial sustainability, is variable. Future priorities in Bishkek include extending collection to unserved communities; improving landfill standards; increasing recycling rates through informal sector cooperation; improving data availability; and engaging all stakeholders in waste management strategy decisions. Extending the scope and flexibility of the ISWM protocol is recommended to better represent the variation in conditions that occur in waste management systems in practice